Damage Detection in Holed Carbon Fiber Composite Laminates Using Embedded Fiber Bragg Grating Sensors Based on Strain Information. (7th December 2020) - Ding, Guoping; Song, Wenhao; Gao, Xiaoling; Cao, Hao
Abstract : Compared with metal materials, Carbon Fiber Reinforced Plastic (CFRP) is more excellent in performance, with high specific strength and high specific modulus. And among various CFRP structural elements, CFRP laminated plates have widespread applications. However, some indiscernible and hidden primary damage always appears on the CFRP laminated plate and will continuously evolve and expand after being loaded. This work starts with the analysis of the relationship between the changes of the strain distribution and damage expansion of CFRP laminated plates and proposes the damage recognition method of CFRP laminated plates based on strain information. Then, the CFRP laminate damage monitoring system based on Fiber Bragg Grating (FBG) sensor is established, and the CFRP laminate damage identification experiment based on FBG sensor is made to verify the accuracy of the CFRP laminate damage identification method. The results show that the maximum error between the load when the damage appears on the FBG sensor and that when the damage of CFRP laminated plates expands based on the simulated analysis does not exceed 16%. The accuracy of the damage recognition method of CFRP laminated plates is verified and the damage recognition of CFRP laminated plates and their expansion process is achieved.